ABOUT THE ISSUE OF FOREIGN LANGUAGE TRAINING IN THE SYSTEM OF LIFELONG LEARNING - Lashuk, Nataliia; Hrechok, Lidiia; Kormiltsyna, Svitlana (Educological discourse, 2021)
The current paper attempts to examine the issues of lifelong education. According to UNESCO documents the notion of lifelong education is defined. The advantages of lifelong learning are highlighted. The lifelong educational system should meet the needs of society, as well as take into account the positive approaches and experience of the development of the world and domestic educational systems. The paper mentions the difficulties of adult lifelong learning as lack of time or lack of conditions for safe relevant learning environment, limitation of learning by specific goals and objectives, use of relevant knowledge or skills in various settings or contexts. The paper focuses on the principles of lifelong education and the issues to be tackled in the context of their implementation: what methods, techniques and strategies to choose to involve students’ previous system of knowledge, enhance their performance, reflection, control over the learning process. The importance of foreign language training in the process of foreign language communicative competence formation and the role of a foreign language as a tool of cognition and acquisition of knowledge are analyzed. It is established that a foreign language is an important component of professional training of specialists in any field of knowledge. A combination of methods for the development of critical and creative thinking, cooperative learning, problem-based, project-based methods as effective for the formation of foreign language communicative competence of adults is proposed. The importance of continuity between the stages of mastering a foreign language and the use of formative assessment of the previous system of knowledge is emphasized. The strategies «INSERT», «Know-Want to Know-Learned», the creation of mind maps for establishing a connection with previous and acquired system of knowledge and identifying prospects in adults foreign language training are proposed.